EffECT Of MULTI ENZYME SUPPLEMENTATION ON ILEAL DIGESTIBILITIES Of DRY MATTER, PROTEIN, ETHER EXTRACT, PHYTATE PHOSPHORUS AND NON-STARCH POLYSACCHARIDES IN BROILER DIET - A. Bharathidhasan (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A biological trial was conducted to study the effect of multi enzyme supplementation on ileal digestibilities of dry matter (DM), crude protein (CP), ether extract (EE), phytate phosphorus (PP) and non-starch polysaccharides (NSPs) in terms of neutral detergent fibre (NDF), acid detergent fibre (ADF), hemicellulose and cellulose in broilers for a period of 0-6weeks. The broilers used in this trial were fed diets supplemented with enzyme at 0, 250, 500, 750 and 1000 g/ton of feed with a proportionate reduction in metabolizable energy (ME-1.25, 2.5, 3.75 and 5 %), crude protein (CP-0.75, 1.5, 2.25 and 3 %), methionine + cytine (0.5, 1, 1.5 and 2 %) and available phosphorus (2.2, 4.4, 6.6 and 8.8 %). The level of individual enzyme per gram of multi enzyme supplement was cellulase 146 IU, xylanase 241 IU, pectinase 98 IU, protease 74 IU, amylase 778 IU and phytase 33 IU. The ileal digestibility was conducted on 6 th week of trial. The ileal DM digestibility (%) was significantly (p